Tuberculosis and silicosis burden in artisanal and small-scale gold miners in a large occupational Health outreach programme in Zimbabwe - Moyo, Dingani; Zishiri, Christopher; Ncube, Ronald; Madziva, Godknows; Sandy, Charles; Mhene, Reginald; Siziba, Nicholas; Kavenga, Fungai; Moyo, Florence; Muzvidziwa, Orippa; Ncube, Petronella; Chigaraza, Blessings; et al. (MDPI, 2022)
Artisanal and small-scale miners (ASMs) labour under archaic working conditions and are exposed to high levels of silica dust. Exposure to silica dust has been associated with an increased risk of tuberculosis and silicosis. ASMs are highly mobile and operate in remote areas with near absent access to health services. The main purpose of this study was to evaluate the prevalence of tuberculosis, silicosis and silico-tuberculosis among ASMs in Zimbabwe. A cross-sectional study was conducted from 1 October to 31 January 2021 on a convenient sample of 514 self-selected ASMs. We report the results from among those ASMs who attended an outreach medical facility and an occupational health clinic. Data were collected from clinical records using a precoded data proforma. Data variables included demographic (age, sex), clinical details (HIV status, GeneXpert results, outcomes of chest radiographs, history of tuberculosis) and perceived exposure to mine dust. Of the 464 miners screened for silicosis, 52 (11.2%) were diagnosed with silicosis, while 17 (4.0%) of 422 ASMs were diagnosed with tuberculosis (TB). Of the 373 ASMs tested for HIV, 90 (23.5%) were sero-positive. An HIV infection was associated with a diagnosis of silicosis. There is need for a comprehensive occupational health service package, including TB and silicosis surveillance, for ASMs in Zimbabwe. These are preliminary and limited findings, needing confirmation by more comprehensive studies.